IoT-Based Flood Monitoring System using ESP32 - Lias, Jais; Kumaran, Gneskumar (Evolution in Electrical and Electronic Engineering, 2024)
This work aims to develop an IoT-based flood monitoring system using ESP32 that detects the water depth level to alert authorities and nearby people. The system utilizes a TOF10120 laser sensor, an LCD, an ESP32, an ESP32 cam, and 3 LEDs as indicators and a buzzer. The system detects water depth levels and categorizes flood severity into three ranges, triggering corresponding LED lights and audible alerts. The green LED indicates an alert level (1401-2000 mm), the yellow LED a warning level (801-1400 mm), the red LED a danger level flood situation (1401-2000 mm) and a buzzer as an alarm. The ESP32 module facilitates wireless connectivity, enabling remote monitoring and alert notifications via smartphone applications. Implementing this IoT-based flood monitoring system offers several advantages, including early detection of flood situations, prompt alerts to concerned authorities and nearby people, and the ability to monitor and manage flood conditions remotely. Such a system can significantly contribute to reducing the impact of floods by enabling timely responses and proactive measures to mitigate potential damages. The IoT application is Blynk. An ESP32 cam is also included as an additional feature to monitor water depth levels visually. Additionally, an LCD is integrated to provide continuous updates on the water depth level as a Blynk notification.